UNDERSTANDING SHARIA INVESTMENT DECISIONS AMONG MEMBERS OF THE TDA BONE BUSINESS COMMUNITY: THE ROLE OF FINANCIAL BEHAVIOR - Muh. Farid Muntashir; Sitti Nikmah Marzuki; Jumriani (Jurnal Ilmiah Al-Tsarwah, 2026)
This study aims to analyze the influence of the TDA Bone Business Community on financial behavior in making sharia investment decisions. The study is motivated by the important role of business communities in improving financial literacy, shaping financial behavior, and encouraging awareness of investment practices based on Islamic principles among community members. This research employed a quantitative approach using questionnaire distribution with a Likert scale to members of the TDA Bone Business Community. The sample consisted of 80 respondents selected proportionally. Data analysis was conducted through validity testing, reliability testing, and simple linear regression analysis using the Statistical Package for the Social Sciences (SPSS). The findings reveal that the TDA Bone Business Community has a positive and significant influence on financial behavior in sharia investment decision-making. This result is evidenced by the coefficient of determination value of 57.2%, indicating that the community variable provides a strong contribution to members’ financial behavior. Furthermore, the significance value obtained was lower than 0.05, confirming that the research hypothesis was accepted. The findings indicate that community activities, access to information, financial education, and social interaction are capable of enhancing financial literacy and increasing members’ awareness in making investment decisions based on sharia principles. This study is expected to contribute to the development of Islamic economics literature and serve as a reference for business communities in designing more effective, sustainable, and adaptive financial education programs to strengthen healthy financial behavior among community members in the future.